Obesity Is Associated With Progression of Atherosclerosis During Statin Treatment. Issue 7 (July 2016) - Sandfort, Veit; Lai, Shenghan; Ahlman, Mark A.; Mallek, Marissa; Liu, Songtao; Sibley, Christopher T.; Turkbey, Evrim B.; Lima, João A. C.; Bluemke, David A.
Abstract : Background: This study aimed to determine the relationship of statin therapy and cardiovascular risk factors to changes in atherosclerosis in the carotid artery. Methods and Results: Carotid magnetic resonance imaging was used to evaluate 106 hyperlipidemic participants at baseline and after 12 months of 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase inhibitor (statin) treatment. Multivariable logistic regression was used to determine factors associated with progression (change in carotid wall volume >0) or regression (change ≤0) of carotid atherosclerosis. Computed tomography coronary calcium scores were obtained at baseline for all participants. The median age was 65 years (interquartile range 60–69 years), and 63% of the participants were male. Body mass index >30, elevated C‐reactive protein, and hypertension were associated with increased carotid wall volume (obesity: odds ratio for progression 4.6, 95% CI 1.8–12.4, P <0.01; C‐reactive protein: odds ratio for progression 2.56, 95% CI 1.17–5.73, P =0.02; hypertension: odds ratio 2.4, 95% CI 1.1–5.3, P <0.05). Higher statin dose was associated with regression of carotid wall volume ( P <0.05). In multivariable analysis, obesity remained associated with progression ( P <0.01), whereas statin use remained associated with regression ( P <0.05). Change in atheroma volume in obese participants was +4.8% versus −4.2% in nonobese participants ( P <0.05) despite greater low‐density lipoprotein cholesterol reduction in obese participants. Conclusions: In a population with hyperlipidemia, obese patients showed atheroma progression despite optimized statin therapy. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01212900.